Temporal diabetes-induced biochemical changes in distinctive layers of mouse retina - Aboualizadeh, Ebrahim (Sci Rep, 2018)
To discover the mechanisms underlying the progression of diabetic retinopathy (DR), a more comprehensive understanding of the biomolecular processes in individual retinal cells subjected to hyperglycemia is required. Despite extensive studies, the changes in the biochemistry of retinal layers during the development of DR are not well known. In this study, we aimed to determine a more detailed understanding of the natural history of DR in Akita/+ (type 1 diabetes model) male mice with different duration of diabetes. Employing label-free spatially resolved Fourier transform infrared (FT-IR) chemical imaging engaged with multivariate analysis enabled us to identify temporal-dependent reproducible biomarkers of the individual retinal layers from mice with 6 weeks,12 weeks, 6 months, and 10 months of age. We report, for the first time, the nature of the biochemical alterations over time in the biochemistry of distinctive retinal layers namely photoreceptor retinal layer (PRL), inner nuclear layer (INL), and plexiform layers (OPL, IPL). Moreover, we present the molecular factors associated with the changes in the protein structure and cellular lipids of retinal layers induced by different duration of diabetes. Our paradigm provides a new conceptual framework for a better understanding of the temporal cellular changes underlying the progression of DR.